Pembuktian Serta Kualifikasi Unsur Pidana Terhadap Tindak Pidana Narkotika Jenis Tembakau Sintetis di Indonesia - Buana, Andika Prawira; Ramadhan, Muhammad Fauzi; Suhra, Andi Amalia; Kaisar, Kaisar (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This study aims to analyze the process of evidence against the crime of narcotics synthetic Tobacco species regulated in Article 114 and Article 112 of law no. 35 Of 2009 On Narcotics. The research method used is normative legal research, which examines and interprets relevant legal regulations, legal documents, and legal doctrines in the context of evidence against synthetic tobacco narcotics crimes. This research is the latest research because there is no scientific work such as dissertation, thesis, thesis, national or International Journal that specifically discusses the evidence against synthetic Tobacco narcotics crimes under Article 114 and Article 112 of law no. 35 Of 2009 On Narcotics. The results showed that the legal qualification against synthetic Tobacco narcotics offense, as stipulated in Article 112 paragraph (2) and Article 114 paragraph (2) of law no. 35 of 2009 on narcotics, found a legal vacuum because synthetic tobacco is not clearly included in the classification of Narcotics Group I both derived from plants and non-plants, due to differences in sources, manufacturing processes, chemical composition, and effects on users. Regulations such as Kepmenkes No. 246 / Menkes/SK / 2017 on narcotics, ago guidelines No. 18 of 2021, and Perkap No. 6 of 2019 concerning the investigation of criminal offenses does not provide clarity regarding the classification of synthetic tobacco as Class I narcotics. In the aspect of criminal evidence against synthetic Tobacco narcotics, the evidence is carried out in a similar way to natural marijuana, which is a narcotic plant type i, where the entirety of synthetic tobacco is weighed, causing ambiguity in law enforcement.